Women And White-Collar Crime: Interview for CPJM’s Scientific Journal: Women And White-Collar Crime: Interview for CPJM’s Scientific Journal - Dodge, Mary (Revista Científica do CPJM, 2023)
Women And White-Collar Crime: Interview for CPJM’s Scientific Journal - PHD, Professor of Criminal Justice at the University of Colorado, Denver, School of Public Affairs.